2018
DOI: 10.1002/tafs.10030
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Seining Detection Probability for Fishes of Great Plains Sand‐Bed Rivers

Abstract: Species detection error (i.e., imperfect and variable detection probability) is an essential consideration when investigators map distributions and interpret habitat associations. When fish detection error that is due to highly variable instream environments needs to be addressed, sand‐bed streams of the Great Plains represent a unique challenge. We quantified seining detection probability for diminutive Great Plains fishes across a range of sampling conditions in two sand‐bed rivers in Oklahoma. Imperfect det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 66 publications
(140 reference statements)
1
14
0
Order By: Relevance
“…Unequal or insufficient effort within sites may explain some of the ranges in detection probability reported in recent fisheries studies. A study examining detection probability of Great Plains minnows in two Oklahoma rivers reported relatively low detection probability of Arkansas River shiner Notropis girardi based on four seine hauls per 200 m site, and suggested >10 hauls were required to mitigate detection bias (Mollenhauer et al, 2018). In the Pecos River of New Mexico, single‐pass seining produced a poor representation of the fish assemblage, failing to detect many species that were present at all sites during depletion sampling (Widmer et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Unequal or insufficient effort within sites may explain some of the ranges in detection probability reported in recent fisheries studies. A study examining detection probability of Great Plains minnows in two Oklahoma rivers reported relatively low detection probability of Arkansas River shiner Notropis girardi based on four seine hauls per 200 m site, and suggested >10 hauls were required to mitigate detection bias (Mollenhauer et al, 2018). In the Pecos River of New Mexico, single‐pass seining produced a poor representation of the fish assemblage, failing to detect many species that were present at all sites during depletion sampling (Widmer et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…For seining, there is little information available on the effects of within‐site effort on catch‐rates and assemblage metrics. We recommend 2.5 times the within‐site effort used by Mollenhauer et al (2018) as the minimum effort in order to reduce the amount of variability in catch due to under sampling within a site. We suggest that four hauls per 200 m reach was too few, whereas 40 was too many.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Habitat measurements were taken following each fish sampling bout. Given that sampling efficiency can differ based on species and environmental conditions (Gwinn, Beesley, Close, Gawne, & Davies, ; Mollenhauer, Logue, & Brewer, ), we examined how pool and riffle depths differed across sampling events to ensure sampling efficiency did not confound results. Because sampling only occurred during base‐flow conditions, we found that mean pool and riffle depths were relatively constant at these sites (Figure S1) with mean depths typically within 0.1 m in pools and 0.05 m in riffles for most of the sampling events, never differing more than 0.5 m across sampling events.…”
Section: Methodsmentioning
confidence: 99%